Ciclo de nutrientes : fenología de la abscisión y dinámica de la descomposición en distintas especies caducifolias y perennifolias - Garrido M.V.; Del Arco J.-M.; Escudero A. (Jornadas sobre las bases ecológicas para la gestión en ecosistemas terrestres, 1989)
The process of litter decomposition ten shows initial stages with an intense mineralization, because of leaching and decomposition of labile constituents. These dynamics imply strong pulses of nutrient inputs to soil, which can increase leaching losses. In this paper, comparisons between different species show that leaf litter shed at the start of a climatically unfavourable season decomposes more gradually, with dynamics more or less linear. On the contrary, leaves shed at the start of favourable periods show initial phases of stronger weight loss, which conforms, to more or less negative exponential dynamics of weight loss. The first kind of abscission phonology is very common among evergreen Mediterranean species that typically shed their leaves at the start or during the dry season. Accordingly, this kind of phonology of leaf abscission can provide a more gradual return of nutrients to soil compared to the abscission habits of deciduous species.
Jornadas sobre las Bases Ecológicas para la Gestión en Ecosistemas Terrestres, 1988/06/13-15, Zaragoza (Spain)